Partial Gravity Compensation of a Surgical Robot - Maaroof, Omar Waleed Najm; Dede, Mehmet İsmet Can; Saeed, Saad Zaghlul; Dede, Mehmet İsmet Can (SAGE Publications Inc., 2021)
Surgical robots are safety-critical devices that require multiple domains of safety features. This article focuses on the passive gravity compensation design optimization of a surgical robot. The limits of this optimization are related with the safety features including minimization of the total moving mass/inertia and compactness of the design. The particle swarm optimization method is used as a novel approach for the optimization of a parallel remote-center-of-motion mechanism. A compact design is achieved by partially balancing the mechanism, which also decreases the torque requirements from the actuators. © The Author(s) 2021.
Keywords: Partial gravity compensation; Particle swarm optimization; Remote-center-of-motion mechanisms